60 ans d’Union Indienne ? - Dalal Benbabaali (EchoGéo)
After 60 years of Independence, India is projecting herself as a symbol of « unity in diversity ». Though the democratic institutions, the developmental efforts and the policy of reservations have promoted national integration, the rhetoric of Indian unity, rooted in the freedom movement, tends to ignore the factors of divisiveness created by social and regional inequality. Ethnic, religious and caste identities, which are used for partisan ends, are often leading to violent conflicts. The continuing exclusion of the masses in spite of economic growth tends to prove that the benefits of Independence have been cornered by a few sections of the population.